Determinan Revitalisasi Pasar Pon Trenggalek - Bella Dwi Cahyanti; Khoirul Fuddin (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
This study aims to find out how the Moda, the cost of renting a place, the number of hours worked, the amount of loss, and the income of the Pon Market traders before and after the revitalization. The analytical tool used is a different test, namely the Paired T Test, and the Wilcoxom-signed Rank Test. The results showed that there was no significant difference in capital before and after revitalization, namely the value of Asymp Sig. (2-tailed) of 0.104, the cost of renting aplace there is a significant difference before and after revitalization with the value of Asymp Sig. (2-tailed) of 0.000, the number of working hours there is no significant difference before and after revitalization with the Asymp Sig value. (2-tailed) of 0.30, the amount of Loss there is a significant difference before and after Revitalization with the Asymp Sig value. (2-tailed) of 0.01, Income there is a significant difference before and after Revitalization with the value of Asymp Sig. (2-tail) of 0.000.